DAKWAH PADA ERA GLOBAL - Dalinur M Nur (Fakultas Dakwah dan Komunikasi, Universitas Islam Negeri, Raden Fatah Palembang, 2014)
This paper talks about dakwah in the global era. In this global era as disclosed above relative regional barriers fade with tools of communication technology. Everything is a challenge for dakwah Islamiyah if preaching Islamic thought activity does not take part in the process. The formulation of the problem to be addressed in this study is a global of dakwah Islamiah? Or whether Islam is in line with the prevailing globalization process? The fact that there is and texts are found in the Qur'an shows that Islam is the religion of Islam global. It means that is intended for mankind on this earth without exception, do not look at race, color or ethnicity differences in language capable. The expression of the Prophet Muhammad,